1675d Knowledge transfer and exchange in work and health: reaching workplace audiences. (24th April 2018) - Van Eerd, D
Abstract : Introduction: Workplace injury and illness can be burdensome for individual workers, workplaces, medical systems, insurance systems and society as a whole. The notion of research to practice is important in work and health research. Konwledge transfer and exchange (KTE) is the practice of generation synthesis and dissemination of research. The objective of this presentation is to synthesise the literature describing KTE activities relevant to workplace health and safety programs and interventions. Methods: A comprehensive review of the literature was completed. Search strategies developed using terms for knowledge transfer and occupational health and safety were run in six electronic databases. (Medline, Embase, Eric, Social sciences, Web of Science, and Business Source Premier). References of relevant documents and hand-searching complimented the search. Documents that described a KTE approach for workplaces were reviewed. KTE approach data were extracted and synthesised according to a framework by Lavis (2003) (What, To whom, By Whom, How, and With what effect) as well as conceptual guidance. Results: Literature searchers revealed 34 documents that described 23 different KTE approaches designed to reach workplaces. The KTE approaches addressed workplace and intermediary audiences. KTE methods and outcomes varied greatly according to the context. However, there were common elements including targeting workers as a key audience involving researchers in dissemination and using multi-dissemination methods. Dissemination method consistently included direct interaction but also often featured printed materials. Many KTE approaches were guided by conceptual frameworks. However, no single conceptual framework was predominant. Conclusion: Common elements related to audience, activities and impact were found in the literature that can help to guide future KTE approaches. Including workers as an audience and researchers as disseminators in a multi-faceted approach along with in-person meetings and printed material are important aspects of KTE for work and health. Conceptual guidance was content dependent.